2021
DOI: 10.3390/jcm10214926
|View full text |Cite
|
Sign up to set email alerts
|

Shaft Fractures in Patients Requiring Primary or Revision Total Knee Arthroplasty Can Be Successfully Treated with Long-Stemmed Implants without Additional Fixation

Abstract: The aim of this study was to evaluate the bone union, complication rate, clinical and functional outcomes of long-stemmed total knee arthroplasty (TKA) in patients with periprosthetic femoral or tibial shaft fractures and in patients with femoral or tibial shaft fractures with coexisting advanced knee osteoarthritis (OA). This retrospective study comprised 25 patients who underwent surgery due to tibial or femoral shaft fractures: (1) with coexisting severe knee OA or (2) with a periprosthetic fracture requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, the results from a study conducted by Tarity et al [17] led to the authors conclusion that, for TKA patients, FS implants may be helpful in avoiding the complication of PPF. Finally, although not directly related to the prevention of PPF, one study found that patients who experience PPF can be successfully treated with revision TKA utilizing long-stemmed TKA [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the results from a study conducted by Tarity et al [17] led to the authors conclusion that, for TKA patients, FS implants may be helpful in avoiding the complication of PPF. Finally, although not directly related to the prevention of PPF, one study found that patients who experience PPF can be successfully treated with revision TKA utilizing long-stemmed TKA [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although not directly related to the prevention of PPF, one study found that patients who experience PPF can be successfully treated with revision TKA utilizing longstemmed TKA. 18 While the overall incidence of PPF after TKA is relatively low, that number may be underestimated when looking specifically at the high fracture risk patient population. Previously identified risk factors for PPF after TKA include neurologic disease, chronic steroid use, rheumatoid arthritis, osteoporosis, female sex, and advanced age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, it is crucial to measure the range of motion (ROM) of the knee/hip. Unfortunately, in this context, lateral radiography is widely recognized as the gold standard [ 5 ], but for normal post-operative complete knee/hip arthroplasty examination, radiographs of the knee/hip in both acute flexion and extension (or ab/adduction for the hip) are not indicated due to the risk of overexposing the patient to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of cases, doctors simply use a goniometer or an inclinometer for measuring the angular range when the patient is within the hospital structure and do not have any control on the patient movements during exercises at home. Both instruments are poorly accurate for this kind of measurement, since a digital inclinometer appreciates a 6° minimum significant difference while the goniometer-based measurement could lead to even larger errors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%